PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK KARAKTER PEDULI SOSIAL SISWA: STUDI DI SMP ISLAM QURANI AL-BAHJAH - Pratama, Fikri Rizky; Sundawa, Dadang; Komalasari, Kokom (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the implementation of Civic Education (PKn) in instilling social care values among students at SMP Islam Qurani Al-Bahjah. Using a qualitative case study approach, data were obtained through observations, in-depth interviews, and document analysis. The findings indicate that the development of social care values is carried out through the integration of the national curriculum with the school’s Islamic culture, manifested in social project activities, value habituation, teacher role modeling, as well as the synergy between civic and religious activities. Values such as empathy, cooperation, solidarity, mutual assistance, and social responsibility were found to develop significantly among students, as reflected in the increased prosocial behavior and heightened sensitivity to environmental needs. The main supporting factors include the school’s religious culture, strong teacher support, and a conducive pesantren-based environment, while the challenges include the heterogeneity of student characteristics, limited instructional time for Civic Education, and external environmental influences. These findings demonstrate that an integrative Civic Education model grounded in religious values can strengthen the formation of students’ social care character and make a significant contribution to the development of value-based civic education